Selected blood parameters with potential diagnostic application in the course of inflammation in chronically obese individuals undergoing bariatric surgery - Bracha, Marietta; Szady-Grad, Małgorzata (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2023)
Bariatric surgery has been recognized as the most effective long-term treatment for obesity. It leads to radical and permanent weight loss, improved quality of life and reduced risk of metabolic diseases. The search for a potential mechanism responsible for the pathogenesis of obesity-related diseases has revealed a close relationship between excess nutrients and the development of inflammation. An increasing number of studies on the impact of bariatric surgery on the level of inflammatory parameters in the blood proves a decrease in systemic inflammation.